2019
DOI: 10.5398/tasj.2019.42.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Productivity of Brown Midrib Sorghum Mutant Line Patir 3.7 (Sorghum bicolor L. Moench) Treated with Different Levels of Nitrogen Fertilizer

Abstract: The study aimed to determine the best of nitrogen fertilizer level based on growth and biomass production of brown midrib sorghum mutant line Patir 3.7. This research was conducted at the Field Laboratory in the Faculty of Animal Science, Andalas University, Padang. The experiment was assigned in a completely randomized block design with 4 levels of nitrogen fertilizer application and 3 replications. The treatments consisted of N0= 0 kg N ha-1 as a control; N1= 50 kg N ha-1 ; N2= 100 kg N ha-1 ; and N3= 150 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
2
10
1
Order By: Relevance
“…leaf width. The results of this study are lower than those reported [10,12] The responses of several parameters due to the treatment of harvest time and the administration of urea fertilizer on sorghum samurai I and the 2nd cutting (ratoon 1) can be seen in Table 2. All agronomic parameters produced in samurai sorghum I at the 2nd cutting (ratoon 1) showed no interaction (p >0.05) due to different harvest times and urea fertilizer application.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…leaf width. The results of this study are lower than those reported [10,12] The responses of several parameters due to the treatment of harvest time and the administration of urea fertilizer on sorghum samurai I and the 2nd cutting (ratoon 1) can be seen in Table 2. All agronomic parameters produced in samurai sorghum I at the 2nd cutting (ratoon 1) showed no interaction (p >0.05) due to different harvest times and urea fertilizer application.…”
Section: Resultscontrasting
confidence: 77%
“…Plant height due to harvest time and dose Different fertilizer applications resulted in the same value (p >0.05), meaning that the treatment used did not affect plant height parameters. Results The plant heights obtained ranged from 217.00 -243.80 cm higher than reported [10,11] that 164, 86 -184, 18 cm and 214.38 cm in sorghum brown midrib.…”
Section: Resultsmentioning
confidence: 66%
“…BMR mutations are phenotypically portrayed by the presence of brown vascular tissues in the leaf edge and sheath as well as in the stem (Rao et al, 2012). BMR sorghum results from a genetic mutation that contains fewer lignin compounds (Green et al, 2014;Sriagtula et al, 2021) and is a promising forage source because of these low-lignin characteristics (Sriagtula et al, 2019). The BMR type contains less cell wall content than standard forage sorghum (Astigarraga et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum (Sorghum bicolor L. Moench) is the most produced crop in the world after wheat, rice, maize, and barley (Dahir et al, 2015). Sorghum has a wide adaptation and low input to grow on marginal lands (Mathur et al, 2017;Sriagtula et al, 2019). Sorghum has higher lignin content, which limits its consumption by ruminant animals due to conventional varieties of sorghum used is as a food and industrial crop (Sriagtula et al, 2017).…”
Section: Introductionmentioning
confidence: 99%